Valorisation of crustacean and bivalve processing side streams for industrial fast time-to-market products: A review from the European Union regulation perspective - Yang Zou; Marc Heyndrickx; Jane Debode; Katleen Raes; Donatella de Pascale; Patrice Behan; Michelle Giltrap; Christine O’Connor; Runar Gjerp Solstad; Kjersti Lian; Themistoklis Altintzoglou; Ragnhild Dragøy; et al. (Frontiers in Marine Science, 2023)
A massive amount of crustaceans and bivalves are consumed each year, leading to millions of tons of processing side streams from the seafood industry. Considering the current trend of (bio)circular and zero-waste food production, crustacean and bivalve processing side streams (CBPS) seem a promising and emerging resource for producing high-value-added products. This paper highlights the general composition of CBPS with high commercial values, namely, protein, lipids, carotenoids, minerals and chitins. The extraction strategies of these fractions, including conventional chemical and environmentally friendly methods, are also discussed. This review presents and summarises CBPS as raw materials for developing fast time-to-market products complying with specific EU regulations, including animal feeds, bio-pesticide/stimulants, and cosmetic ingredients. This paper also provides insights into challenges of applying CBPS as raw materials to generate products for human consumption.

Current Status of the Red King Crab ( Paralithodes camtchaticus ) and Snow Crab ( Chionoecetes opilio ) Industries in Norway - Grete Lorentzen; Gøril Voldnes; Ragnhild D. Whitaker; Ingrid Kvalvik; Birthe Vang; Runar Gjerp Solstad; Marte R. Thomassen; Sten I. Siikavuopio (Reviews in Fisheries Science & Aquaculture, 2018)